Analisis Pengaruh Brand Equity dan Perceived Product Quality terhadap Customer Value - Rita Rita; Felix Felicio Kumayas (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The purpose of this research is to examine the relationship and influence of Brand Equity, and Perceived Product Quality on Customer Value and have impact toward Purchase Intention of Mosquito Trap Zz One on company PT Global Indoraya Lestari. The respondent of this study is consumer that domiciled in Jakarta. This study uses Structural Equationg Model method to measure the relationship and influence between independent and dependent variables. In this study collected data uses questionnaire spread and achieve 100 respondent. The result of this study show the significance of relationship and influence of Brand Equity and Perceived Product Quality on Customer value toward Purchase Intention. But have one variables Perceived Product Quality not have significance individualy toward Purchase Intention on mosquito trap Zz One. FFK